Réponses

2013-11-17T17:30:56+01:00
Bonsoir


A = 5/6 -5/2 x 8/15
Tu commences par la multiplication
A = 5/6 - 40/30
A = 25/30 -40/30 = -15/30 = -1/2

B = (6/7 -3/4) x 8/3
B = (24/28 - 21/28) x 8/3
B = 3/28  x 8/3
B = 24/ 84 = 2/7

C = 5/9 - 8/5 : 3/4
C = 5/9 - 8/5 x 4/3
C = 5/9 - 32/15
c = 75/135 - 288/135 = -213/135 = -71/45


2013-11-17T17:42:45+01:00
5/6 - 5/2 x 8/15 = 5/6 -  (5 x 8) / (2 x 15)
= 5/6 - 40/30
= 5/6 - 4/3
= 5/6 - 8/6
= -3/6
= -1/2


(6/7-3/4) x 8/3
=[( 6 x 4) / (7 x 4) - (3 x 7) / (3 x 7)] x 8/3
= (24/28 - 21/28) x 8/3
= 3/28 x 8/3
=(3 x 8) / (28 x 3)
= (24 / 84) : 12
= 2/7


5/6 - 8/5 : 3/4
= 5/6 - 8/5 x 4/3
= 5/6 - (8 x 4)/(5 x 3)
= 5/6 - 32/15
= (5 x 5)/(5 x 6) - (32 x 2)/(15x2)
= 25/30 - 64/30
= -39/30